Development of cylindrical cavity resonator technique for magnetic loss measurement in yttrium iron garnet - Rodziah, Nazlan; Farah Nabilah, Shafiee; Idza Riati, Ibrahim; Mohamad Ashry, Jusoh; Ros Azlinawati, Ramli; F., Esa (Penerbit Universiti Malaysia Pahang, 2024)
Cavity resonators are essential as high-sensitivity sensors, capable of detecting small changes in electromagnetic fields or material properties, owing to their ability to generate strong fields at resonance. However, due to budget constraints limiting access to advanced technology, developing a custom-built cavity resonator can be a more cost-effective alternative to purchasing commercially available resonators. Building on this motivation, a cylindrical cavity resonator was designed and fabricated specifically for microwave loss measurement, focusing on C-band frequencies. The performance of the fabricated resonator was assessed through COMSOL simulations and experimentally validated by measuring transmission loss with a vector network analyzer connected to the resonator, where a spherical yttrium iron garnet (YIG) sample was employed as a tested material. The simulation result of the magnetic field radiation pattern validates the performance and efficacy of the fabricated cavity resonator. The S21 parameter measurements revealed a transmission loss of -62.2 dB for the empty resonator, while the YIG-filled resonator exhibited a transmission loss of -57.87 dB under 0 kOe and increased to -23.13 dB when a magnetic field of 0.5 kOe was applied. The increase in transmission loss can be attributed to the changes in the magnetic properties of YIG under the influence of the external magnetic field. This resulted in enhanced resonance conditions where coupling between EM waves and the samples leads to improved resonance conditions and reduced losses, as the alignment of magnetic moments improves the coupling between electromagnetic waves and the materials, which is associated with the ferromagnetic resonance of YIG.